2021
DOI: 10.2319/030121-164.1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of maxillary canine impaction using eruption pathway and angular measurement on panoramic radiographs

Abstract: Objectives To compare the normal eruption pattern and angulation in impacted maxillary canines using panoramic radiographs to predict maxillary canine impaction. Materials and Methods Patients aged 6 to 15 years were classified into the normal eruption group (n = 229) and the impaction group (n = 191). At least two panoramic radiographs were taken in the normal eruption group during the eruption process of the maxillary canin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Most of the studies[ 15 26 27 28 ] which evaluated the eruptive movement of canine, first premolar, and lateral incisor are retrospective, and no study has evaluated the normal pre-eruptive angulations of the canine, lateral incisor, and first premolar during 6–12 years of age. In this study, orthopantomograph, which is a two-dimensional image of a three-dimensional object, was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies[ 15 26 27 28 ] which evaluated the eruptive movement of canine, first premolar, and lateral incisor are retrospective, and no study has evaluated the normal pre-eruptive angulations of the canine, lateral incisor, and first premolar during 6–12 years of age. In this study, orthopantomograph, which is a two-dimensional image of a three-dimensional object, was used.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al . [ 28 ] also stated that the angle between the canine and the lateral incisor in a normal erupting canine will first increase and then decrease as the canine approaches the cervical area of the lateral incisor. This results in the ugly duckling stage and will self-correct after the canine has fully erupted into the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies [ 8 , 15 , 25 , 26 ] that evaluated the eruptive movement of canine, first premolar, and lateral incisor were retrospective, and no study has evaluated the normal pre-eruptive angulations of the C, LI, and FP in children aged 6–12 years. In the present study, orthopantomography [ 15 ] was used, which is a two-dimensional image of a three-dimensional object.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al [ 26 ] also stated that the angle between C and LI in a normal erupting C will first increase and then decrease as the C approaches the cervical area of the LI. This results in the “ugly duckling” stage and will self-correct after the C has fully erupted into the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 87 patients with UCLP reported congenital absence of the permanent lateral incisor on the cleft side in 48.8% of patients (Tortora et al, 2008). Canine angulation has also been noted as an indicator for canine impaction risk, with one study reporting a higher risk for permanent canines angled greater than 30 degrees from the long axis of the lateral incisor in noncleft populations (Shin et al, 2022). A recent study evaluating a cohort of males with UCLP found a higher incidence of canine impaction in patients with missing laterals and canine angulations greater than 25 degrees relative to the midsagittal plane (Hong et al, 2022).…”
Section: Associated Dental Anomaliesmentioning
confidence: 99%